Bridging Into the Future Through Education - Simões, N.; Crespo, N. (Promoting Entrepreneurship to Reduce Graduate Unemployment, 2022)
One of the major bottlenecks of the Portuguese labor market is the level of educational attainment of the population. Despite considerable evolution over the last decades, the country is still behind the European Union average in most education indicators. In 2009, 69.2% of the population aged between 15 and 64 had less than upper secondary education, a value that is more than double the European average. Due to the measures and reforms that have been introduced, in 2019, this proportion had dropped to 47.6%. Between 2009 and 2019, self-employed persons had education levels below the average of the working population. In 2009, 79.0% had less than upper secondary education, and in 2019, this number was still at 50.6%. The human capital of the self-employed persons has significant consequences on their entrepreneurial activities. The low educational attainment level of the population has demanded extensive reforms. This chapter discusses the main policies implemented to improve educational attainment and obtain a comprehensive overview of labor market and education indicators.